Media Tabuspiel dalam Pembelajaran Kosakata Bahasa Jerman - Annisa Puspitasari; Mantasiah R (Universitas Negeri Makassar, 2022)
Abstract. The purpose of this study was to determine the effectiveness of Tabuspiel media in learning German vocabulary for class XI MIA students of SMA Negeri 9 Makassar. The type of research was a quasi-experimental (nonequivalent control group design). This study consists of two variables, namely the independent variable and the dependent variable. The independent variable was the use of Tabuspiel media and the dependent variable was student learning outcomes, namely mastery of German vocabulary. The population of this study was 60 students of class XI MIA SMA Negeri 9 Makassar, class XI MIA 5 as the experimental class and class XI MIA 6 as the control class. The sample used is total sampling. The instruments used in this study were multiple choice questions and matching questions. Data analysis used the Independent Sample T-test which showed that the value of tcount > ttable 3,822 > 2,001717 and the value of sig. (2-tailed) 0,000 < 0,05 at a significance level of 0,05. This showed that Tabuspiel media is effective in learning German vocabulary for students of class XI MIA SMA Negeri 9 Makassar.Keywords: Media, Tabuspiel, vocabulary learning, German.